Explaining Brand Loyalty through Brand Quality: Brand Trust as Mediator and Brand Love as Moderator - Conny Conny (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the effect of brand quality on brand trust and brand loyalty among Netflix customers in Kendari City. It also investigates the mediating role of brand trust in the relationship between brand quality and brand loyalty, as well as the moderating role of brand love in the relationship between brand trust and brand loyalty. A quantitative explanatory design was employed using survey data from 160 Netflix customers selected through purposive sampling. The research instrument used a five-point Likert scale, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that brand quality has a positive and significant effect on brand trust and brand loyalty. Brand trust also has a positive and significant effect on brand loyalty. Furthermore, brand trust mediates the effect of brand quality on brand loyalty, while brand love strengthens the relationship between brand trust and brand loyalty. These findings indicate that Netflix customer loyalty is formed through a combination of quality-based evaluation, trust-based confidence, and emotion-based attachment. Practically, Netflix needs to maintain content quality, application stability, account security, and service consistency while strengthening emotional connections through personalized experiences and engaging content. Academically, this study contributes to branding literature by integrating mediation and moderation mechanisms in explaining loyalty toward digital streaming services.